Association of Sinonasal Computed Tomography Scores to Patient‐Reported Outcome Measures: A Systematic Review and Meta‐analysis. (29th January 2023) - Chen, Tiffany; Chidarala, Shreya; Young, Gabrielle; Jeong, Seth S.; Nguyen, Shaun A.; Edwards, Thomas S.; Schlosser, Rodney J.
Abstract: Objective: To perform a systematic review of proposed sinus computed tomography (CT) scoring systems and determine their association with patient‐reported outcome measures (PROMs). Data Sources: PubMed, CINAHL, Scopus, and Cochrane Library. Review Methods: A systematic search was conducted following the PRISMA guidelines (Preferred Reporting Items for Systematic Reviews and Meta‐analyses) for studies describing CT scores and PROMs in patients with chronic rhinosinusitis. Results: A total of 144 studies were included. Out of 20, 741 patients, 53.6% were male and 55.5% had nasal polyposis. A meta‐analysis of correlations revealed a moderate correlation between Lund‐McKay (LM) and the 22‐item Sinonasal Outcome Test (SNOT‐22; r = 0.434, P < .001) and a weaker correlation between LM and the 20‐item Sinonasal Outcome Test (SNOT‐20; r = 0.257, P = .039). Meta‐regression also revealed a weak association between LM and SNOT‐20 (n = 25 studies) but no significant associations between Zinreich score and SNOT‐22 or LM scores and PROMs, including SNOT‐22 (n = 94 studies), Rhinosinusitis Disability Index (n = 25), nasal obstruction visual analog scale (n = 15), Chronic Sinusitis Survey (n = 12), Total Nasal Symptom Score (n = 4), Total Symptom Score (n = 3), and 12‐Item Short Form Health Survey (n = 3). Conclusion: There is essentially little association between radiologic grade and PROMs. CT grading systems with improved clinical utility are needed.